When the Clouds Roll By - Stover, Franklin (Flicker Alley, 2008)
"When the Clouds Roll By" was one of Fairbanks’s last romantic comedies before his switch to larger pictures, and one of his best. The story of a superstitious young underachiever who is unwittingly being manipulated by his boss and by a crazy doctor, the film was written by Fairbanks and directed by Victor Fleming. Fleming, a no-nonsense "man’s man", went on to become one of Metro-Goldwyn-Mayer’s most reliable directors of classics, including "The Wizard of Oz" (1939) and "Gone with the Wind" (1939). Fleming keeps the action in "When the Clouds Roll By" moving at a fast pace, using brisk editing to stay one jump ahead of the audience. More importantly, he allows Fairbanks to show off the acrobatic abilities that soon took his career in a different direction. Using ingenious movie trickery, Fairbanks even pre-dates a famous Fred Astaire sequence by more than 30 years. Wisely, the acrobatics are plot driven. As Fairbanks said, "I have never in the pictures performed a stunt for the stunt’s sake. Such athletic things as I have done on the screen were done to get over my interpretation, my idea of youth." [www.silentfilm.org]
Keywords: DVD-Video